'Hybridity' in the novels of Ananda Devi - Kistnareddy, Oulagambal Ashwiny (2011)
Hybridity is a term that has garnered a great deal of attention in the postcolonial world and has considerable critical purchase in the contemporary world. Its proponents, from Bakhtin (1981) and Bhabha (1994) to more recent theorists of hybridity in its various forms are many. However, it also has many dissidents. Hybridity’s ambiguous status as a colonial, negative term that has been reappropriated to undermine notions of purity and essentialism, can be quite problematic. Nevertheless, in its more positive aspects, it can prove to be quite enabling for postcolonial intellectuals like Ananda Devi. Devi expresses this point of view in an interview where she speaks of herself as being ‘hybride dans le bon sens du terme’ (Indes Réunionnaises 2003). This thesis examines Devi’s novels in order to gauge the extent to which these can be read through the lens of hybridity, especially given the recent reference to texts emanating from the Indian Ocean as being hybrid (Hawkins 2007, Prabhu 2007). Chapter One investigates the positive aspects of hybridity that Devi underlines in her interview, namely her ability to use the different cultures and traditions at her disposal in her writing. The chapter demonstrates the linguistic hybridity (Bakhtin 1981) and formal hybridity of the novels, which is the result of Devi’s own upbringing in multicultural society. The subsequent two chapters focus on what can be interpreted as the negative aspects of hybridity. The second chapter explores the psychological dislocations of Devi’s characters who cannot reconcile two identities either because they are made to choose one identity over the other or because they do not have the memory of the ancestral past. This chapter looks at Bhabha’s notion of hybrid identities (1994), in order to determine whether this concept of ‘hybrid identities’ is possible in Devi’s novels. The third chapter explores the concept of hybrid bodies using theories of the grotesque (Bakhtin 1984 and others), suggesting ways in which Devi uses othered bodies in order to undermine the notion of categorised identity and social classification that is prevalent in the Mauritian society she depicts.